Clinical Effect of Steroid Administration in Patients with Chronic Impingement Syndrome on Postoperative Arthroscopic Subacromial Decompression - Yıldız, Vahit; Aydın, Ali; Kalalı, Fatih; Yıldırım, Ömer Selim; Topal, Murat; Aydın, Pelin (Fırat University, 2012)
Objective: We aimed in our study to investigate the effect of intraarticular corticosteroid injection applied to patients with the chronic impingement syndrome after arthroscopic subacromial decompression on the clinical result. Materials and Methods: We employed in our study a total of 44 (24 males, 20 females) patients with chronic impingement syndrome to whom intraarticular corticosteroid injection was applied before arthroscopic subacromial decompression between 1-7 times. We measured clinically Constant scores of those patients before and after arthroscopic subacromial decompression. We compared the correlation between the number of intraarticular corticosteroid injections and clinic scores and statistically the clinic results after and before arthroscopic subacromial decompression. Results: While the average Constant score of patients to whom intraarticular corticosteroid injection was applied 2.57 times on average is 15.27 (range 2-52), the average Constant score after arthroscopic subacromial decompression was 71.30 (range 2-90). The correlation was observed between the number of intraarticular corticosteroid injection and clinic results before arthroscopic subacromial decompression (P0.001). Conclusion: There is no correlation between the number of intraarticular corticosteroid injections applied to patients with chronic impingement syndrome and clinic results after arthroscopic subacromial decompression.

Amaç: Çalışmamızda Kronik impingement sendromlu hastalara uygulanan intraartiküler kortikostreoid enjeksiyonun, artroskopik subakromiyal dekompresyon sonrası klinik sonuca etkisini araştırmayı amaçladık. Gereç ve Yöntem: Artroskopik subakromiyal dekompresyon öncesi 1-7 defa arası intraartiküler kortikostreoid enjeksiyon uygulanan kronik impingement sendromlu toplam 44 (24 erkek, 20 kadın) hastayı çalışmamıza aldık. Artroskopik subakromial dekompresyon öncesi ve sonrası Constant skorlarını ölçerek istatiksel olarak karşılaştırdık. Bulgular: Ortalama 2.57 defa intraartiküler kortikostreoid enjeksiyonu uygulanan hastaların ortalama Constant skorunu 15.27 (dağılım 2-52), Artroskopik subakromiyal dekompresyon sonrasında ortalama Constant skorunu 71.30 (dağılım 2-90) ölçtük. İntraartiküler kortikostreoid enjeksiyon adedi ile artroskopik subakromiyal dekompresyon öncesi klinik sonuçlar arasında istatistiksel olarak anlamlı bir fark olmasına karşın (P0.001). Sonuç: Kronik impingement sendromlu hastalara uygulanan intraartiküler kortikostreoid enjeksiyonu adedi ile artroskopik subakromiyal dekompresyon sonrası klinik sonuçlar arasında bir ilişki bulunmamaktadır.
Kronik İmpingement Sendromlu Hastalarda Uygulanan Steroidin Artroskopik Subakromiyal Dekompresyon Sonrasına Klinik Etkisi